1987
DOI: 10.1101/gad.1.9.1014
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosome assembly in yeast.

Abstract: Downloaded from 5p11ce050me a55em61y 1n yea5t 5nRNA5 have 6een 5h0wn t0 6e a550c1ated w1th the 5p11-ce050me (P1k1e1ny et a1. 1986., 2. H05t0m5ky et a1., unpu61.; N. R1ede1 et a1., per5. c0mm.}, and we 5ha11 pr0-v1de further ev1dence f0r 5uch a550c1at10n5 1n th15 paper. 7he c011ect10n 0f yea5t 5nRNA5 115ted 1n 7a61e 1 have 6een further 1mp11cated 1n mRNA 5p11c1n9 6ecau5e they are prec1p1tated 6y a human aut01mmune ant15erum 5m 1M. J0ne5 and C. 6uthr1e, per5. c0mm.} a5 are the1r mamma11an c0unterpart5. 7h15 ant1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
478
1
4

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(512 citation statements)
references
References 47 publications
(4 reference statements)
29
478
1
4
Order By: Relevance
“…The presence of crn-like TPR elements in several RNAprocessing proteins (McLean & Rymond, 1998) suggested that Clf1p might also contribute to pre-mRNA splicing+ To test this, the efficiency of yeast pre-mRNA splicing was monitored as a function of time after transcriptional repression of GAL1::CLF1+ Metabolic depletion of Clf1p clearly inhibited pre-mRNA splicing as RP51A (and ACT1, see below) mRNA levels dropped and pre-mRNA levels increased with incubation in the glucose-based medium (Fig+ 3A)+ The time course of splicing impairment and the subsequent growth arrest were indistinguishable from what has been previously reported for other GAL fusions, such as PRP8 (Brown & Beggs, 1992) and the genes for TPR proteins Prp39p (Lockhart & Rymond, 1994) and Prp42p (McLean & Rymond, 1998)+ No Clf1p-dependent changes in RNA mobility were observed with several intron-free pol II transcripts, including the U2 snRNA (Fig+ 3B)+ Primer extension analysis confirmed that the more slowly migrating RNAs observed with RP51A and actin (ACT1) hybridization probes were largely due to increased levels of pre-mRNA and not the similarly sized lariat intermediate (Fig+ 4 and data not shown)+ From these results we conclude that the growth arrest observed after GAL1::CLF1 repression results from a defect in cellular pre-mRNA splicing+ Extracts prepared from yeast cultures depleted of Clf1p were unable to process exogenously added premRNA (Fig+ 5A)+ This splicing deficiency was associated with a specific defect in spliceosome assembly (Fig+ 5B)+ When splicing reactions were resolved by native polyacrylamide gel electrophoresis, pre-mRNA from the Clf1p-complete extract was rapidly assembled into the U1, U2-containing prespliceosome band (complex A, Fig+ 5B)+ As expected based on previous studies (Pikielny et al+, 1986;Cheng & Abelson, 1987), the prespliceosome was converted with time into the more slowly migrating, snRNP-complete spliceosome band (complex B, Fig+ 5B)+ In contrast to the wildtype extract, a single splicing complex band formed in the Clf1p-depleted extract that comigrated with the well-characterized prespliceosome complex+ Prespliceosome arrest is clearly not a de facto consequence of inhibited growth or pre-mRNA splicing, as depletion of other essential splicing factors block assembly at earlier or later times in assembly (e+g+, see Lockhart & Rymond, 1994;McLean & Rymond, 1998;Xie et al+, 1998)+ The time of appearance and level of abundance of the putative Clf1-defective presplice- osome were similar to that observed for the wild-type prespliceosome, indicating that Clf1p-depletion did not significantly impair earlier steps in splicing complex assembly+…”
Section: Spliceosome Assembly Is Impeded In the Absence Of Clf1psupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of crn-like TPR elements in several RNAprocessing proteins (McLean & Rymond, 1998) suggested that Clf1p might also contribute to pre-mRNA splicing+ To test this, the efficiency of yeast pre-mRNA splicing was monitored as a function of time after transcriptional repression of GAL1::CLF1+ Metabolic depletion of Clf1p clearly inhibited pre-mRNA splicing as RP51A (and ACT1, see below) mRNA levels dropped and pre-mRNA levels increased with incubation in the glucose-based medium (Fig+ 3A)+ The time course of splicing impairment and the subsequent growth arrest were indistinguishable from what has been previously reported for other GAL fusions, such as PRP8 (Brown & Beggs, 1992) and the genes for TPR proteins Prp39p (Lockhart & Rymond, 1994) and Prp42p (McLean & Rymond, 1998)+ No Clf1p-dependent changes in RNA mobility were observed with several intron-free pol II transcripts, including the U2 snRNA (Fig+ 3B)+ Primer extension analysis confirmed that the more slowly migrating RNAs observed with RP51A and actin (ACT1) hybridization probes were largely due to increased levels of pre-mRNA and not the similarly sized lariat intermediate (Fig+ 4 and data not shown)+ From these results we conclude that the growth arrest observed after GAL1::CLF1 repression results from a defect in cellular pre-mRNA splicing+ Extracts prepared from yeast cultures depleted of Clf1p were unable to process exogenously added premRNA (Fig+ 5A)+ This splicing deficiency was associated with a specific defect in spliceosome assembly (Fig+ 5B)+ When splicing reactions were resolved by native polyacrylamide gel electrophoresis, pre-mRNA from the Clf1p-complete extract was rapidly assembled into the U1, U2-containing prespliceosome band (complex A, Fig+ 5B)+ As expected based on previous studies (Pikielny et al+, 1986;Cheng & Abelson, 1987), the prespliceosome was converted with time into the more slowly migrating, snRNP-complete spliceosome band (complex B, Fig+ 5B)+ In contrast to the wildtype extract, a single splicing complex band formed in the Clf1p-depleted extract that comigrated with the well-characterized prespliceosome complex+ Prespliceosome arrest is clearly not a de facto consequence of inhibited growth or pre-mRNA splicing, as depletion of other essential splicing factors block assembly at earlier or later times in assembly (e+g+, see Lockhart & Rymond, 1994;McLean & Rymond, 1998;Xie et al+, 1998)+ The time of appearance and level of abundance of the putative Clf1-defective presplice- osome were similar to that observed for the wild-type prespliceosome, indicating that Clf1p-depletion did not significantly impair earlier steps in splicing complex assembly+…”
Section: Spliceosome Assembly Is Impeded In the Absence Of Clf1psupporting
confidence: 61%
“…The native gel assay results suggested that tri-snRNP addition was impaired in the Clf1p-depleted extract+ However, because the electrophoretic mobility of a Clf1p-deficient spliceosome cannot be predicted with certainty, it remained possible that the U4, U5, or U6 snRNA bound in the absence of Clf1p+ If so, then the Clf1p-defective complex would need to be viewed as more elaborate than the normal prespliceosome+ To address this issue, splicing complexes were affinity purified on biotin-substituted pre-mRNA and then assayed for snRNA content by Northern blot (Fig+ 6)+ When a Clf1HAp-complete control extract was used, each of the spliceosomal snRNAs was recovered with the biotinylated RP51A pre-mRNA (Fig+ 6, lane 4)+ As previously observed (Pikielny et al+, 1986;Cheng & Abelson, 1987;Konarska & Sharp, 1987;Xie et al+, 1998), the U4 snRNA was underrepresented in the mature splicing complexes (Fig+ 6, lane 4) relative to the unfractionated extract (Fig+ 6, lane 1) due to U4 release prior to 59 splice site cleavage+ The U1 and U2 snRNAs, but few U4, U5, or U6 snRNAs, were recovered from splicing complexes assembled in the Clf1p-depleted extract (Fig+ 6, lane 3)+ Equivalent snRNA profiles were observed with earlier (5 and 15 min) time points of assembly in the Clf1p-depleted extract (data not shown)+ In all cases, however, the U1 and U2 snRNA recovery was substrate dependent, as virtually no snRNA copurified with a nonbiotinylated control substrate RNA (Fig+ 6, lane 5) or on RNAs lacking splice sites (Rymond et al+, 1987 and data not shown)+ The low level of tri-snRNP-derived snRNA in the Clf1p-defective complexes was not due to general degradation in the extract, as the U4, U5, and U6 snRNAs were abundantly present in the unbound fraction (Fig+ 6, lane 2)+ Together with the data presented above these results show Phenotypic assay of growth in the presence or absence of Clf1p+ Yeast cultures containing the wild-type CLF1 gene (CLF1) and the clf1::HIS3 disruptant transformed with GAL1::CLF1 or its viable mutant derivative GAL1::clf1(679) were streaked on galactose-based rich medium (GAL) or glucose-based medium (GLU) and incubated at 30 8C+ C: Complementation by the Drosophila crn gene+ Wild-type yeast (CLF1) and the clf1::HIS3 disruptant transformed with TEF::crn were streaked on YPD medium and incubated at 30 8C+ FIGURE 3. Analysis of cellular pre-mRNA splicing after Clf1p-depletion+ A: Wild-type yeast (CLF1) and the GAL1:CLF1 yeast culture were grown continuously on galactose (T ϭ 0) or shifted to glucose-based medium for the indicated times+ Total cellular RNA was extracted at each time point and then resolved on a denaturing agarose-formaldehyde gel+ A: The results of hybridization with the intron-containing RP51A probe+ The positions of the pre-mRNA and mRNA are schematically represented at the left of the image+ B: The same filter after hybridization with the SNR20 U2 snRNA gene+ that the U4/U6+U5 tri-snRNP particle does not bind productively to the prespliceosome in the absence of Clf1p+ Weak or transient interactions between the trisnRNP and prespliceosome might occur without Clf1p, but such interactions are insufficient to support premRNA splicing in vivo or in vitro+ Splicing in the Clf1p-depleted extracts was partially reconstituted with a hemagglutinin-tagged Clf1p protein (ClfHAp) synthesized in a rabbit reticulocyte lysate ( The results presented above suggest that Clf1p likely promotes spliceosome assembly through TPR-based interactions that help organize the U4/U6+U5 tri-snRNP particle or help tether this particle to the prespliceosome+ Consistent with the latter suggestion, twohybrid studies revealed that Clf1p interacts with at least two components of the yeast commitment complex a...…”
Section: Spliceosome Assembly Is Impeded In the Absence Of Clf1pmentioning
confidence: 87%
“…Splicing is catalyzed by the spliceosome, a large, dynamic RNA-protein complex that takes on various forms through the different steps of splicing (Konarska and Sharp, 1986;Cheng and Abelson, 1987;Nilsen, 1994;Burge et al, 1999;Yu et al, 1999;Karijolich and Yu, 2008;Will and Lührmann, 2011). Spliceosome activity depends on a large number of protein components, as well as five "uridyl-rich" snRNAs-U1, U2, U4, U5, and U6.…”
Section: Introductionmentioning
confidence: 99%
“…The high evolutionary conservation of U6 and the release (or less-tight association) of U4 from the spliceosome prior to intron cleavage (Pikielny et al, 1986;Cheng & Abelson, 1987;Lamond et al, 1988) has led to the further suggestion that U6 is the enzymically active component, and that the role of V4 is to act as a carrier for U6 and to block its activity until the appropriate moment. However, it is notable that only a part of the region of highest primary sequence conservation between V4 from Schizo pombe and vertebrates corresponds to the V4jU6 interaction domain.…”
Section: Discussionmentioning
confidence: 99%
“…Major events in spliceosome assembly include the association of UI and U2 small nuclear ribonucleoproteins (snRNPs) with the 5' splice junction and site of branch formation, respectively. U4 and U6 snRNA are associated by hydrogen-bonding and are found in a single snRNP particle (Bringmann et al, 1984;Hashimoto & Steitz, 1984) and may associate with the spliceosome as a U4/U5/U6 complex; U4 is released from the spliceosome before intron cleavage (Pikielny et al, 1986;Cheng & Abelson, 1987;Lamond et al, 1988). The site and mechanism of action of U4 snRNP remains obscure but it is essential for splicing activity in vitro.…”
Section: Introductionmentioning
confidence: 99%